PENGEMBANGAN MEDIA PETRA (PETA NUSANTARA) BERBASIS COOPERATIVE LEARNING PADA KELAS IV DI SDN PENJARINGAN 03 JAKARTA UTARA - Putri Yohana; Nidya Chandra Muji Utami; Arita Marini (Universitas Negeri Medan, 2023)
The Development Of Learning Media In Form Of Board Games Based On Cooperative Learning In The Content Of Social Studies Learning Grade IV Elementary School. This research and development aims to develop a learning media called